2008
DOI: 10.1001/archpsyc.65.10.1146
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Second-Generation Antipsychotic Medication on Smooth Pursuit Performance in Antipsychotic-Naive Schizophrenia

Abstract: Context Analyses of smooth pursuit eye movement parameters in patients with schizophrenia provide information about the integrity of neural networks mediating motion perception, sensorimotor transformation, and cognitive processes such as prediction. Although pursuit eye tracking deficits have been widely reported in schizophrenia, the integrity of discrete components of pursuit responses and the effect of second-generation antipsychotic medication on them are not well established. Objective To examine diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 70 publications
3
28
1
Order By: Relevance
“…It is well-known that eye-movement parameters are affected by certain drugs, especially those that affect the central nervous system. Benzodiazepines and second-generation antipsychotics can alter eye movements (e.g., generating a decrease in saccadic peak velocity [68], [69]), but they might also affect other eye-movement parameters. Therefore, we have expressed our results regarding medication in terms of CED.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that eye-movement parameters are affected by certain drugs, especially those that affect the central nervous system. Benzodiazepines and second-generation antipsychotics can alter eye movements (e.g., generating a decrease in saccadic peak velocity [68], [69]), but they might also affect other eye-movement parameters. Therefore, we have expressed our results regarding medication in terms of CED.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this impairment is not affected by dopamine D2 receptor antagonist antipsychotics (Tanabe et al, 2006;Thaker, 2007;Lencer et al, 2008), but is also attenuated by NIC administration (by cigarette smoking, NIC patch, or nasal spray) among patients with schizophrenia (Martin and Freedman, 2007). A recent fMRI study by Tanabe et al (2006) showed that NIC improves abnormal SPEM in schizophrenia through modulation of hippocampal and anterior cingulate activity (Tanabe et al, 2006).…”
Section: Antipsychotic Treatment and The Cholinergic Systemmentioning
confidence: 99%
“…6 However, across all studies published since 1993 (which include all open-loop studies and a large subset of closed-loop studies), open-loop pursuit measures have yielded a medium effect size, d of −0.45 (±0.47, n = 12), whereas closed-loop pursuit gain has yielded a large effect size, d , of −0.87 (±0.42, n = 42). For measures of both open- and closed-loop pursuit, deficits have been found even in neuroleptic naĂŻve and unmedicated patients (Hutton et al 1998; Sweeney et al 1998a, 1999; Thaker et al 1999; Lencer et al 2008). These findings suggest that if motion processing deficits contribute to ETD, higher-order processes that would normally compensate for motion processing deficits are affected as well.…”
Section: Pathophysiology Of Etdmentioning
confidence: 99%